2021
DOI: 10.1002/advs.202003156
|View full text |Cite
|
Sign up to set email alerts
|

Nb2O5‐Based Photocatalysts

Abstract: Photocatalysis is one potential solution to the energy and environmental crisis and greatly relies on the development of the catalysts. Niobium pentoxide (Nb 2 O 5 ), a typically nontoxic metal oxide, is eco-friendly and exhibits strong oxidation ability, and has attracted considerable attention from researchers. Furthermore, unique Lewis acid sites (LASs) and Brønsted acid sites (BASs) are observed on Nb 2 O 5 prepared by different methods. Herein, the recent advances in the synthesis and application of Nb 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 363 publications
0
50
0
Order By: Relevance
“…To date, several outstanding reviews have provided extensive summaries in this area, including the application of acid catalysis by Nb 2 O 5 to reactions of carboxylic acid derivatives, 25 biomass conversion over niobium-based catalysts 26 and Nb 2 O 5 -based photocatalysts. 27 However, as far as we know, no review has focused on the unique role of Nb 2 O 5 in supported metal catalysts for lignin hydrodeoxygenation. Herein, we summarize the recent advances in Nb 2 O 5 -supported metal catalysts for lignin hydrodeoxygenation and will introduce the following aspects: the structure, acid and redox properties of Nb 2 O 5 , the unique contributions of Nb 2 O 5 including its role in the promotion of C-O cleavage and the enhancements of suitability and reusability in the aqueous phase.…”
Section: Yaxuanmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several outstanding reviews have provided extensive summaries in this area, including the application of acid catalysis by Nb 2 O 5 to reactions of carboxylic acid derivatives, 25 biomass conversion over niobium-based catalysts 26 and Nb 2 O 5 -based photocatalysts. 27 However, as far as we know, no review has focused on the unique role of Nb 2 O 5 in supported metal catalysts for lignin hydrodeoxygenation. Herein, we summarize the recent advances in Nb 2 O 5 -supported metal catalysts for lignin hydrodeoxygenation and will introduce the following aspects: the structure, acid and redox properties of Nb 2 O 5 , the unique contributions of Nb 2 O 5 including its role in the promotion of C-O cleavage and the enhancements of suitability and reusability in the aqueous phase.…”
Section: Yaxuanmentioning
confidence: 99%
“…2. 33 Importantly, Su et al 27 concluded that the unique acidity of Nb 2 O 5 was relevant to the adsorption-activation process in reactions. In most cases of solid-acid-catalyzed lignin HDO reactions, 34 the acid property facilitates C-O bond cleavage, which indicates that Nb 2 O 5 can be an excellent support or catalyst.…”
Section: Acid Propertymentioning
confidence: 99%
“…Recently, niobiumbased metal-oxide photocatalysts have attracted extensive attention owing to their special electronic structure and chemical stability. [19][20][21][22] The valence electrons in the outermost layer of Nb-containing have a unique electron configuration and can be controlled by mixing valence states and hybridizing with the outer electron orbitals of O, S, N, and C atoms in the corresponding compounds. [23][24][25] In recent years, except for some related works about the photocatalytic hydrogen evolution reaction and degradation of organic pollutants, there are few reports on the artificial photosynthesis of CO 2 photoreduction over Nb 2 O 5 -based nanocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its excellent dielectric properties, Ta 2 O 5 is used in dynamic random access memory chips, field effect transistors, thin-film electroluminescence devices, biological and chemical sensors, antireflection coatings for silicon solar cells, charge-coupled devices, corrosion-resistant materials, optical wave guides, and thin-film resistors [ 8 ]. Nb 2 O 5 , on the other hand, exhibits strong redox abilities and unique Lewis and Brønsted acid sites, and as a result has been used for photocatalytic activities [ 9 ]. Another application of Nb 2 O 5 has been in the fabrication of resistive random memory access devices because of the dependence of its dual electrical response of memory and threshold switching behaviors on oxygen contents resistive to random memory access devices [ 10 ].…”
Section: Introductionmentioning
confidence: 99%